B-Cell lymphoma 2 Protein Expression and Established Clinicopathologic Features in Breast Cancers. (11th September 2019) - Xiang, Yan; Li, Li; Zarella, Mark; Brzezinska, Katarzyna; Hosny, Kareem; Hou, Steve; Garcia, Fernando
Abstract: Objectives: B-cell lymphoma 2 (Bcl-2) proto-oncogene alterations are involved in tumor genesis and play a vital role in regulating cell apoptosis. The objective of this research is to determine the prognostic value of quantitative expression of the Bcl-2 protein in breast cancer. Methods: This study investigated a series of 158 primary breast cancers for Bcl-2 protein expression. Results were correlated with clinicopathologic features (age, tumor size, tubule formation, nuclear pleomorphism, mitotic count, and Nottingham prognostic index: NPI) and a panel of markers of established or presumed predictive values. Results: Bcl-2 H-score (multiplied by staining intensity and percentage of positive cells) was observed to have a significant reversed correlation with the Magee Equation 1, 2, 3 ( P 1 < .001, P 2 < .001, P 3 < .001, r 1 = –0.36, r 2 = –0.34, r 3 = –0.34). High proliferative activity as assessed by Ki-67 (>25%) staining negatively associated with Bcl-2 H-score ( P = .03). Low Bcl-2 H-score was associated with old age (age >63, P = .039). Bcl-2 cytoplasm percent positive score was negatively associated ( P = .02, n = 92) with overexpression of p53 (positive percentage >1.5). High Bcl-2 H-score was also associated with tumor size (T >1.5 cm, P = .034), but there was no significant correlation observed between Bcl-2 expression and the NPI calculated using the size of the lesion, the number of involved lymph nodes, and the grade of the tumor (NPI >3.4, P = .317). Conclusion: (1) This study reports a correlation between Bcl-2 H-score and all three Magee equation values. (2) Bcl-2 H-score provides prognostic value better than percentage of positive cells. (3) This study further reports a correlation between Bcl-2 H-score and age, tumor size, Ki-67, and p53, irrespective of the type of adjuvant therapy received and across molecular subtypes. Collectively, these results establish the rationale for introduction of semiquantitative expression of the Bcl-2 protein to improve prognostic stratification of breast cancer patients.